Pelatihan Pembuatan Pupuk Organik untuk mengurangi penggunaan Pupuk Kimia di Dusun Dasan Geria Utara, Dasan Geria, Lombok Barat - Isrowati; Ahmad Jupri; Immy Suci Rohyani; Lalu Muhammad Aby Dujana; Baiq Fadila Arlina; Annisa Nur Janah Djaelani (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Dasan Geria Utara Hamlet exhibits significant potential for organic waste generation, primarily Organic biomass such as foliage litterand domestic kitchen residues. Currently, waste management practices in this region remain suboptimal, thereby adversely affecting environmental sanitation. Concurrently, the local community encounters challenges regarding the availability and accessibility of synthetic fertilizers. Hence, an intervention program focusing on organic fertilizer production is imperative to mitigate reliance on chemical fertilizers and to optimize the utilization of available domestic waste streams. This community service project aimed to enhance public knowledge and technical proficiency in manufacturing organic fertilizers. The initiative was executed in three sequential phases: preparation, practical demonstration of organic fertilizer production, and evaluation. The methodologies deployed included socialization, Focus Group Discussions (FGD), and hands-on participatory training guided by experts. The program was successfully implemented, characterized by high participant engagement. The empirical outcomes indicated a substantial increase in the community's literacy regarding the dichotomy between synthetic and organic fertilizers, alongside enhanced technical skills in composting. Evaluation metrics revealed that all participants comprehensively understood the ecological impacts of chemical fertilizers, the advantages of organic alternatives, and successfully demonstrated the capacity to generate organic fertilizer from household waste utilizing easily replicable home-based methods. This program is expected to drive a paradigm shift by reducing synthetic fertilizer dependency and increasing organic fertilizer adoption in Dasan Geria Utara Hamlet, Dasan Geria Village. Ultimately, this capacity-building initiative empowers the community to leverage localized resources, fostering a more sustainable environmental ecosystem.